Dietary intake at stake: Clients' adjusted diagnostic explanations during dietary treatment of malnutrition (risk) - Alyanne Barkmeijer; Hedwig te Molder; Joyce Lamerichs; Harriët Jager-Wittenaar (Elsevier, 2024)
In this article, we show how elderly clients in Dutch dietary consultations adjust dietitians' history taking questions that suggest a cause for weight loss. Using conversation analysis and discursive psychology, we analyzed the history taking phase of recorded primary care conversations of 7 dietitians with 17 clients with malnutrition (risk). In response to the dietitian's history taking question, clients repeatedly present: 1) a problem in which weight loss is presented as unexpected and a conscious reduction in dietary intake is (therefore) not an issue, 2) a problem for which they cannot be held responsible, but which at the same time acts as a reason for reduced dietary intake, 3) a problem in which higher dietary intakes have been recommended by a third party that have proved impracticable. In these adjusted diagnostic explanations, clients emphasize the multidimensionality of their weight loss, which concurrently provides an explanation as to why they cannot be (solely) held responsible for their reduced dietary intake. Clients' adjusted diagnostic explanations make relevant an evaluation by the dietitian. Dietitians' subsequent lack of uptake leads to clients recycling diagnostic explanations to still get a response from the dietitian. Our findings offer insight into improving client-centered counseling by paying attention to clients' adjusted diagnostic explanations.